2018
DOI: 10.5897/ajar2018.12974
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drought on rice cultivation in sub-Saharan Africa and its mitigation: A review

Abstract: Drought is the primary cause of yield loss in agriculture throughout the world, and is currently the most common reason for global food shortages. Three-quarter of the most severe droughts in the last ten years have been in Africa, the continent which already has the lowest level of crop production and drought adaptive capacity. The increased incidences of drought and erratic rainfall have thrown small holder farmers in Africa into deep poverty, hunger and malnutrition. In this paper, the drought situation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Reduced grain yield is a result of morphological responses such as increases in leaf rolling, stomata closure, and leaf tip drying; molecular responses that include changes in gene expression (up/down regulation of transcripts) and the activation of relevant transcription factors and signaling pathways; and physiological and biochemical responses such as reductions in transpiration, photosynthesis, chlorophyll content, membrane stability, stomatal conductance, and increases in osmoprotectants [ 7 ]. Drought stress reduces the performance of rice varieties that are grown worldwide [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced grain yield is a result of morphological responses such as increases in leaf rolling, stomata closure, and leaf tip drying; molecular responses that include changes in gene expression (up/down regulation of transcripts) and the activation of relevant transcription factors and signaling pathways; and physiological and biochemical responses such as reductions in transpiration, photosynthesis, chlorophyll content, membrane stability, stomatal conductance, and increases in osmoprotectants [ 7 ]. Drought stress reduces the performance of rice varieties that are grown worldwide [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drought is also a major factor limiting rice production in SSA [3]. In SSA, rice is more susceptible to drought events because its cultivation largely depends on rainwater; therefore, even a mild drought significantly reduces the productivity of rice [4].…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that these accessions have capacity to close stomata early enough during periods of drought as a biological survival strategy that ensures effective use of available water. Some varieties of African rice are early maturing and are therefore able to escape terminal drought [11]. It has been found to have thin leaves that roll easily during drought thus reducing transpiration and thin roots which have a high soil penetrative capacity thereby helping in extracting water from the soil [12].…”
Section: Genetic Potential and Capacity For Climate Change Adaptationmentioning
confidence: 99%